2022
DOI: 10.1038/s41598-022-21585-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to air pollution and its effect on ischemic strokes (EP-PARTICLES study)

Abstract: It is well known that exceeded levels of particulate matter in the air and other air pollutants harmfully affect the cardiovascular system. Empirical analyses of the effects of these factors on stroke incidence and mortality are still limited. The main objective of our analyses was to determine the association between short-term exposure to air pollutants and stroke incidence in non-industrial areas, more specifically in north-eastern Poland. To achieve this aim, we used data from the National Health Fund on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…We also observed some counterintuitive behaviour for CO at several lags, in line with studies reporting strange patterns with CO at specific lags ( 28 ). However, our multicollinearity test suggests that there is no reason for concern.…”
Section: Discussionsupporting
confidence: 91%
“…We also observed some counterintuitive behaviour for CO at several lags, in line with studies reporting strange patterns with CO at specific lags ( 28 ). However, our multicollinearity test suggests that there is no reason for concern.…”
Section: Discussionsupporting
confidence: 91%
“…In a large cohort of postmenopausal women, there was no association between five analyzed air pollutants and IS occurrence [ 11 ]. Moreover, in a study performed in Poland, it was demonstrated that carbon monoxide (CO) might have a protective effect on IS onset, whereas other air pollutants increased IS-related morbidity on different days after exposure depending on age and sex [ 12 ]. Other unclear matters remaining in the available literature are lag patterns and vulnerability to smog in specific subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Its formation is favored by high atmospheric pressure and low temperature, especially in winter when heat demand increases causing higher emissions of air pollution from household heating systems [ 18 , 19 ]. The adverse effect of Polish smog has been well documented in one of the analyzed cities, as it increased hospitalization rates due to acute coronary syndromes (ACS) and IS [ 12 , 20 ]. However, the influence of air pollution in the other four cities has never been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In the EP-PARTICLES study, the aim was to investigate temporal variations of ischemic stroke incidence in the 'capital of the green lungs of Poland' -Bialystok -and its link with short-term exposure to air pollution [23]. In 11 years, from 2010 to 2020, we recorded 4838 cases of ischemic stroke with a daily mean of 1.3 cases.…”
Section: Ischemic Stroke Morbiditymentioning
confidence: 99%